Choice with probabilistic reinforcement: effects of delay and conditioned reinforcers. - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1991)
Two experiments measured pigeons' choices between probabilistic reinforcers and certain but delayed reinforcers. In Experiment 1, a peck on a red key led to a 5-s delay and then a possible reinforcer (with a probability of .2). A peck on a green key led to a certain reinforcer after an adjusting delay. This delay was adjusted over trials so as to estimate an indifference point, or a duration at which the two alternatives were chosen about equally often. In all conditions, red houselights were present during the 5-s delay on reinforced trials with the probabilistic alternative, but the houselight colors on nonreinforced trials differed across conditions. Subjects showed a stronger preference for the probabilistic alternative when the houselights were a different color (white or blue) during the delay on nonreinforced trials than when they were red on both reinforced and nonreinforced trials. These results supported the hypothesis that the value or effectiveness of a probabilistic reinforcer is inversely related to the cumulative time per reinforcer spent in the presence of stimuli associated with the probabilistic alternative. Experiment 2 tested some quantitative versions of this hypothesis by varying the delay for the probabilistic alternative (either 0 s or 2 s) and the probability of reinforcement (from .1 to 1.0). The results were best described by an equation that took into account both the cumulative durations of stimuli associated with the probabilistic reinforcer and the variability in these durations from one reinforcer to the next.
43 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/070-304-798-844-976 tex.type: [object Object]
Keywords: Animal; Attention; Choice Behavior; Color Perception; Conditioning; Operant; Mental Recall; Pigeons; Probability Learning; Reinforcement Schedule; Support; U.S. Gov't; P.H.S.; Time Perception; adjusting schedule; animal; article; attention; color vision; conditioned reinforcement; decision making; dept.psy; instrumental conditioning; key peck; learning; pigeon; pigeons; recall; reinforcement; reinforcer delay; reinforcer probability; time perception